Petrophysical Properties of the Kahasib Formation in Missan Region, South Iraq - Al-Mukhtar, Khalid; Jassim, Issam; Al-Hussaini, Ban (Iraqi Journal of Science, 2025)
The present paper deals with the study of petrophysical and dynamic properties of (207) plugs which were taken from rock cores of Khasib Formation at five oil wells (No.2, AM-1 AM-2, HF-3, and HU-1) located in Missan area, South of Iraq.A comparison was made for the studied properties deduced from laboratory and from the available well logs. (35) predictive equations are established to estimate the effective porosity, permeability, in terms of the properties that are obtained from resistivity sonic, radioactivity and neutron porosity logs. These equations showed that multiple correlation coefficients (R) have ranged between weak and excellent. Statistical relations regarding the calculated and the observed values of these properties have also been estimated.Using the same procedure, another (25) predictive equations were established for (75) plugs of the reservoir unit at the studied wells, in terms of the properties deduced from well logs. The estimated correlation factors for these equations are generally ranged between fair to very excellent. Also some statistical parameters were established to describe the relations between the observed and the calculated properties.